Low Response of Renin–Angiotensin System to Sodium Intake Intervention in Chinese Hypertensive Patients. Issue 6 (February 2016) - Feng, Weijing; Cai, Qingqing; Yuan, Woliang; Liu, Yu; Bardeesi, Adham Sameer A.; Wang, Jingfeng; Chen, Jie; Huang, Hui
Abstract : Abstract: The interactions of sodium balance and response of renin–angiotensin–aldosterone system are important for maintaining the hemodynamic stability in physiological conditions. However, the influence of short-term sodium intake intervention in the response of renin–angiotensin system (RAS) on hypertensive patients is still unclear. Thus, we conducted a clinical trial to investigate the effects of short-term sodium intake intervention on the response of RAS in hypertensive patients. One hundred twenty-five primary Chinese hypertensive patients were divided into high, moderate, and low sodium groups by 24-hour urinary sodium excretion (UNa + ). All the patients received a 10-day dietary sodium intake intervention with standardized sodium (173.91mmol/day) and potassium (61.53mmol/day). Blood pressure, urinary sodium, urinary potassium, plasma sodium, potassium, creatinine, the levels of plasma renin activity, plasma angiotensin II concentrations (AT-II), and plasma aldosterone concentrations were detected before and after the intervention. Before the intervention, no differences were found in blood pressure and RAS among 3 groups. After standardized dietary sodium intake intervention, both UNa + excretion and systolic pressure decreased in high-sodium group, while they increased in moderate and low-sodium groups. Intriguingly, there were no changes in the levels of plasma renin activity, AT-II, and plasma aldosterone concentrations among 3 groups during the intervention. The present study demonstrated that the influenced sodium excretion and blood pressure by short-term sodium intake intervention were independent of RAS quick response in Chinese hypertensive patients.